Human development index of the rural community in the three major cities along Pahang River and Muar River, Malaysia - Md. Yassin, Sulaiman; Mohamed Shaffril, Hayrol Azril; Hassan, Md. Salleh; Othman, Mohd Shahwahid; Abu Samah, Bahaman; Abu Samah, Asnarulkhadi; Ramli, Siti Aisyah (American-Eurasian Network for Scientific Information, 2011)
Human development is an effort to bring people to freedom and opportunity and bigger chances for developing their well-being. There are a number of human development indexes that have been developed by researchers all around the world and one of the recent one is known as The American Human Development Index. This study intends to use this index in the context of the Malaysian rural community and hopefully there will be very interesting findings if we can see where actually the rural community in Malaysia stands if compared with the community in the well developed countries such as the USA. Hence, the main objective of this study is to investigate the human development index among the rural community living along the Pahang River and Muar River in Malaysia. This is a quantitative study where a developed questionnaire was used. Through a simple random sampling, a total of 900 respondents were selected from three cities along Pahang River and Muar River namely Pekan, Bahau and Muar. Based on the findings, it can be seen that the respondents studied still have a low level of human de velopment index. However, further analysis had identified that respondents in Muar and Bahau do have a moderate level of human development index. ANOVA employed has confirmed to us that there is no significant difference that can be found in terms of human development indexes between the three cities studied.